Multidisciplinary Approach to Managing Recurrent Cerebrospinal Fluid Leak in a Pediatric Patient Following Myelomeningocele Repair - Rawad Chalhoub, MD; Kareem Makkawi, MD; Edwin Chrabieh, MD; Tarek El Hachem, MD; Marwan Hajjar, MD; Amir Ibrahim, MD (Plastic and Reconstructive Surgery, Global Open, 2025)
Summary:. This case report describes the management of a 6-year-old girl with a cerebrospinal fluid (CSF) leak following trauma after a previous myelomeningocele repair. The patient initially presented with a recurrent CSF leak, wound dehiscence, and infection. In an attempt to close the pseudomeningocele, a bilateral latissimus dorsi musculocutaneous flap procedure was performed. Despite this intervention, she developed a persistent CSF leak, which led to infection and dehiscence of the wound at the midline. She then required secondary repair of the dural defect and insertion of a lumbar drain, while the plastic surgery team applied an Integra dermal regeneration template combined with vacuum-assisted closure (VAC) therapy. One week later, the wound showed no signs of infection, and the VAC was removed. One week later, for optimal lumbar drainage, a ventriculoperitoneal shunt was inserted. The patient’s postoperative course was complicated by fever and ileus, both of which resolved with bowel rest and antibiotics. The patient was discharged in stable condition with no further leakage. On follow-up 4 months later, the patient reported no issues. This case illustrated the successful use of a multidisciplinary approach in managing CSF leaks following myelomeningocele repair by using Integra combined with VAC therapy and a ventriculoperitoneal shunt for optimal wound closure and healing.